The Influence of Scarcity Promotion on Impulse Purchase Behavior: A Mediation Analysis of Arousal - Handayani, Wahyu Prabawati Putri; Kurniawati, Dyah; Pitoyo, Didik Joko (Fakultas Ekonomi Universitas Kadiri, 2025)
Flash sales present an opportunity for online marketplaces to stimulate impulse purchases. This study aims to examine and analyze the effect of scarcity promotion on impulse purchases, with arousal serving as a mediating variable. This research employs a quantitative approach. The sample consists of individuals who participated in a live streaming flash sale by Toko Emas Semar Nusantara on TikTok Shop on November 11, 2024. Data were collected using a Google Form distributed via messages to respondents who had made purchases during the live streaming flash sale. The data analysis was conducted using Jeffreys's Amazing Statistics Program (JASP). The findings indicate that scarcity promotion has a positive and significant effect on arousal; arousal, in turn, has a positive and significant effect on impulse purchases. Additionally, scarcity promotion has a positive and significant influence on impulse purchases. Furthermore, arousal serves as a partial mediator between scarcity promotion and the tendency to make impulse purchases. The managerial implication of this study suggests that business owners should focus on scarcity-driven flash sales to stimulate consumer arousal, thereby enhancing impulse purchases. This study aims to provide business owners with insights into effective product marketing strategies on TikTok Shop, supporting increased sales.